Pengembangan Aplikasi untuk Optimasi Jenis Kendaraan dan Penentuan Rute pada Perusahaan Tranportasi - Cindy Himawan (President University, 2018)
Transportation Management System is very needed in optimize efficiency and effectiveness on logistics company. One of the most important part of transportation management system is determining delivery route from a depot to each customer. A lot of studies have been done about determining the best route in a shipping ritation with various algorithms. In the previous research, determination of delivery route is done without any implementation in the application. During the route determination is still done manually it will make a flow process in the company is not maximize. Model development aims to make an implementation application that serves to determine delivery route based on the problem of vehicle routing problem using the nearest neighbour method which is restricted to heavy loads in the transportation. Implementation of route determination an application will be done based on business process in transportation company, named PT. X, so it is necessary to observe the company. Compared to previous research, this research will determine delivery route in application based on the problem of vehicle routing problem using the nearest neighbour method.